Knowledge and Attitude of Agricultural Extension Providers on Use of Agrochemicals in Migori County, Kenya - Ouma , Peter O.; Gichuki , Cecilia; Muthiani , N. (African Journal of Education,Science and Technology (AJEST), 2017)
Migori County located in South Western Kenya is currently experiencing severe environmental problems as a result of use of various agrochemicals in crop cultivation approaches and cropping methods meant to ensure increased economic productivity but are a great threat towards sustainable agriculture. The research explored education background and competence of Agricultural Extension Service Providers against their attitude towards the use of various agrochemicals in Migori County. The County is located between latitude 0 0 24 ‘ South and 0 0 40 ‘ South and longitude0 0 34 ‘ East and 0 0 50 ‘ East. It covers an area of 2,595Km 2 including approximately 478 Km 2 of water surface. The researcher administered a questionnaire with items focusing on environmental effects of agrochemicals was administered to a target population of 1000 persons enlisted in formal employment by agro-industries, government and private sector who specialize in advisory services to farmers and other extension clients in Migori County. A sample of 120 extension service providers obtained by stratified random sampling based on agro ecological zone derived from the study population was used. The research design was descriptive. Data analysis was done by descriptive statistics, frequencies, percentages, means and standard deviations. Hypothesis testing was done using Chi square at 0.05 level of confidence. The results revealed that 62.6% were well educated with 94.4% being professionally trained. However only 9.32% o had proper knowledge on various agrochemicals and only 13.85% had knowledge on their long term effects on the environment. The test on academic and professional training against attitude revealed a χ2 = 72.14. The extension service providers focused on increased production, extending product value and intensive use of agrochemicals at the expense of long term agricultural production. A moderate positive correlation on the need for in service training in sustainable agriculture and professional training was obtained (r= 0.49, p= 0.05) implying that the higher the professional training the more positive their attitude was towards use of agrochemicals. In service training on use of agrochemicals for agriculture as well as establishment of a legal framework to enforce environmental protection was therefore recommended.